A double-blind, placebo-controlled investigation of the effects of fexofenadine, loratadine and promethazine on cognitive and psychomotor function - Hindmarch, I (Blackwell Science Inc, 1999)
AIMS: To assess whether fexofenadine in a range of doses from 80 to 180 mg has any disruptive effects on aspects of psychomotor and cognitive function in comparison with placebo, loratadine and promethazine, an antihistamine known to produce psychomotor and cognitive impairment. METHODS: Twenty-four healthy volunteers received fexofenadine 80 mg, 120 mg and 180 mg, loratadine 10 mg, promethazine 30 mg (as a positive internal control) and placebo in a six-way crossover, double-blind study. Following each dose, subjects were required to perform a series of tests of cognitive function and psychomotor performance at 1.5, 3, 6, 9, 12 and 24 h post dose. The test battery included critical flicker fusion (CFF), choice reaction time (CRT) and assessment of subjective sedation (LARS). Overall levels of activity were monitored by means of wrist mounted actigraphs throughout each of the 24 h experimental periods. RESULTS: Fexofenadine at all doses tested was not statistically different from placebo in any of the tests used and loratadine did not cause any significant impairment of cognitive function. Significant impairments were found following promethazine. Promethazine caused a significant reduction in CFF threshold and this effect was evident up to 12 h post dose (P < 0.05). There was a significant increase in recognition reaction time at 3 and 6 h post promethazine administration, and the drug caused a significant (P < 0.002) increase in the percentage of ‘sleep-like’ activity from actigraph records during the daytime. CONCLUSIONS: Fexofenadine at doses up to 180 mg appears free from disruptive effects on aspects of psychomotor and cognitive function in a study where the psychometric assessments have been shown to be sensitive to impairment, as evidenced by the effects of the verum control promethazine 30 mg.